FORMULASI SEDIAAN SERUM ANTIOKSIDAN DARI EKSTRAK SARI TOMAT (Solanum lycopersicum L.) DAN EKSTRAK KAYU MANIS (Cinnamomum burmannii) SEBAGAI PERAWATAN KULIT - Ariyanti, Evy Lestari; Handayani, Reti Puji; Yanto, Elih Sutisna (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: Tomato (Lycopersicum esculentum Mill) is a natural source of antioxidants. Tomatoes are rich in vitamins A and C, beta-carotene, potassium and the antioxidant lycopene. Apart from tomatoes, cinnamon also has antioxidant properties. The use of tomatoes and cinnamon directly on the skin is considered ineffective, so it needs to be formulated in serum. Objective: This research to determine how to make tomato and cinnamon serum and to determine the stability of the serum seen from the organoleptic test, homogeneity test, pH stability test and preference test. Methods: This research uses action research method (Action Research). The preparation is made with a composition of tomato juice extract and cinnamon extract with a ratio of 3 grams: 0.5 grams and the addition of 1 gram of xanthan gum for F1, 1.2 grams for F2, 1.4 grams for F3. Results: The Results of the organoleptic tests which have been performed showed the presence of changes on the 6th day until the 21st. The pH stability results obtained from 3 serum samples showed that at week 2 there was a change in pH in the preparations stored at room temperature (15-30 ° C). The result of the serum preference test for texture of as much 93.3% in formula 1. the colors of serum 97% in formula 1 and fragrance of as 83.3% in formula 2. Conclusion: the Results of organoleptic test and test favorite formula featured is F1, while the results of the third homogeneity test were stored for 3 weeks in a homogeneous state. The pH test results are still within the skin pH.